Aberrant phosphorylation of signal transducer and activator of transcription 3 protein of the CD4+ T cells in patients with primary immune thrombocytopenia. Issue 5 (July 2018) - Ke, Yang; Li, Feng; Zhan, Yanxia; Wu, Boting; Zou, Shanhua; Ji, Lili; Min, Zhihui; Hou, Jiayun; Sun, Lihua; Chen, Hao; Cheng, Yunfeng
Abstract : N/A: Primary immune thrombocytopenia (ITP) is an autoimmune disorder characterized by decreased platelet count of which dysfunctional cellular immunity in its pathogenesis. Signal transducer and activator of transcription 3 (STAT3) is critical for the differentiation of T cells. The present study was aimed to investigate the STAT3 protein phosphorylation of CD4 + T cells in ITP patients. Fourteen patients of newly diagnosed ITP with complete remission (R group) and other 15 newly diagnosed ITP patients with nonresponse (N group) after corticosteroids therapy were included. Sixteen healthy human volunteers were served as normal controls (C group). Blood samples were collected before and after the therapy. Serum levels of IL-6 were measured by ELISA. The phosphorylation of STAT3 protein (pSTAT3) and the percentage of Th17 cells of the CD4 + T cells were analyzed by flow cytometry. The STAT3 mRNA expression was examined by Real-time PCR. The level of IL-6 in the R group was higher than that in the C group ( P  = 0.02) whereas no difference was found between groups of N and C. The basal level of pSTAT3 in the R group was significantly higher when compared with N group ( P  = 0.002). The percentage of Th17 cells of the CD4 + T cells in the ITP patients was numerically higher than that in the controls ( P  = 0.03). Our results indicate that ITP patient with higher basal level of pSTAT3 might have more favorite response to the corticosteroid therapy, which warrants further investigation on the prognostic role of pSTAT3 in ITP.